Influence of the confining potential on the linewidth of a quantum well - Hien, Nguyen Dinh (Superlattices and microstructures, 2021)
In this theoretical study, we consider in detail the influence of the confining potential on the magneto-optical absorption linewidth (MOALW) of a quantum well for both intersubband and intrasubband magneto-optical transitions. The projection operator method and the profile technique are used to calculate respectively the MO-absorption power and MOALW in both the semiparabolic, parabolic, and the rectangular confining potential quantum wells. The results obtained from the present study show that (i) the MOALW as functions of the structural, material, and external parameters include the confining potential frequency, the well width, the electron density, the temperature, and the magnetic field, as well as Landau level number; (ii) the larger contribution from intrasubband transitions to electron-phonon scattering compared with intersubband transitions for both three type of above confining potentials; (iii) the dependence of the MOALW on the above parameters is found to be the strongest in case of the square confining potential quantum well while it is the weakest in case of the semiparabolic confining potential quantum well for intersubband magneto-optical transitions, however, that for the parabolic confining potential is similar to the rectangular confining potential for intrasubband magneto-optical transitions. Our present calculations accord well with previous experimental studies. •Influence of the confining potential on the linewidth of a quantum well is studied in detail.•Linewidth is affected by confining frequency, temperature, magnetic field, electron density, well-width, and Landau level.•Intersubband transition linewidth is compared with intrasubband one in both three potential wells.•Linewidth in semiparabolic potential well is compared with that in rectangular and parabolic wells.•Quantum confining potential effects significantly on the linewidth of a quantum well.